2002
DOI: 10.1097/00006534-200208000-00044
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aerosolized Fibrin Glue in Face-Lift Surgery

Abstract: The purpose of this study was to report the use of aerosolized fibrin glue in face-lift surgery. A prospective study was conducted of 48 patients undergoing face-lift surgery sequentially assigned into two groups. The first 24 patients underwent face lifts without glue and the next 24 patients with the use of aerosolized fibrin glue. One surgeon (J.P.F.) performed all the face lifts using the same technique. Drains were only used in those patients who did not receive fibrin glue. The amount of bruising and ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 18 publications
4
34
1
Order By: Relevance
“…Clinically, fibrin sealants can be applied utilizing multiple techniques including application through a double barrel syringe or by spray application [128]. Aerosolized fibrin glue is widely used, particularly in plastic surgery [129], however, spraying techniques can alter the properties of the final fibrin mesh [130]. In the double barrel syringe application system, fibrin sealants are administered in a two-component system in which high concentrations of fibrinogen (80–120 mg/mL) are immediately mixed with high concentrations of thrombin (300–600 NIH U/mL) of equal volume at the delivery site.…”
Section: Introduction To Fibrin Based Biomaterialsmentioning
confidence: 99%
“…Clinically, fibrin sealants can be applied utilizing multiple techniques including application through a double barrel syringe or by spray application [128]. Aerosolized fibrin glue is widely used, particularly in plastic surgery [129], however, spraying techniques can alter the properties of the final fibrin mesh [130]. In the double barrel syringe application system, fibrin sealants are administered in a two-component system in which high concentrations of fibrinogen (80–120 mg/mL) are immediately mixed with high concentrations of thrombin (300–600 NIH U/mL) of equal volume at the delivery site.…”
Section: Introduction To Fibrin Based Biomaterialsmentioning
confidence: 99%
“…The use of fibrin sealants for skin graft fixation has been extensively explored in an effort to improve graft adherence and to enhance wound healing, especially in anatomical locations that are difficult to graft and immobilize (Fezza et al ., ; Yildirim et al ., ; Cohen et al ., ). Fibrin sealant was found to be safe and effective for the attachment of skin grafts, with outcomes at least as good as, or better than, staple fixation (Foster et al ., ; Gibran et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Case reports,11,12,31 large series,13,14,3235 and randomized prospective trials27,36,37 support the value of using fibrin sealant in rhytidectomy. Several investigators question some of the reported advantages of this material 3840.…”
Section: Fda Approved Fibrin Sealant For Rhytidectomymentioning
confidence: 92%
“…In a sequential endoscopic series using fibrin sealant for proper brow fixation, a significant improvement in the last 69 patients compared to the first 28 patients was found for eye brow positioning and muscle weakening14 highlighting the fact that there may be a learning curve for the use of fibrin sealant 4. In another sequentially controlled series of first using no fibrin sealant with drains followed by aerosolized fibrin sealant without drains in facelift surgery,32 significant reductions were found in bruising and swelling ( P < 0.0001) as well as operating room time by 13 minutes ( P < 0.0001). No statistically significant reductions in hematomas were found.…”
Section: Fda Approved Fibrin Sealant For Rhytidectomymentioning
confidence: 99%